On the Origins of the Very First Principle as Infinite: The Hierarchy of the Infinite in Damascius and Pseudo-Dionysius the Areopagite - Ottobrini, Tiziano F. (Peitho. Examina Antiqua, 2019)
This paper discusses the theoretical relationship between the views of Damascius and those of Pseudo-Dionysius the Areopagite. While Damascius’ De principiis is a bold treatise devoted to investigating the hypermetaphysics of apophatism, it anticipates various theoretical positions put forward by Dionysius the Areopagite. The present paper focuses on the following. First, Damascius is the only ancient philosopher who systematically demonstrates the first principle to be infinite (traditional Greek thought tended to regard the arkhē as finite). Second, Damascius modifies the concept and in several important passages shows the infinite to be superior and prior to the finite (previously this assumption was held only by Melissus and, sporadically, by Gregory of Nyssa and Plotinus). Third, Damascius’ theory of being (infinite, endless and ultrarational) is the strongest ancient articulation of the nature of the One which is a clear prefiguration of the negative theology developed by Dionysius the Areopagite.